Cocaine-Induced Pneumopericardium: Safe for Discharge? A Case Report and Literature Review - Xavier Galloo; Jan Stroobants; David Yeo; Esmael El-Abdellati (Case Reports in Cardiology)
A 29-year-old male presented at the Emergency Department (ED) with chest pain and neck tenderness after intranasal cocaine usage. Physical exam of the patient demonstrated moderate subcutaneous emphysema on the right side of his neck. The ECG did not demonstrate any changes associated with cocaine-induced cardiac ischemia, and blood analysis was normal (negative troponins). A chest X-ray revealed subtle evidence of pneumomediastinum. Subsequent thoracic CT confirmed the presence of subcutaneous emphysema with a pneumopericardium and a large pneumomediastinum along with a small pneumothorax. The patient was managed conservatively and kept overnight for observation. He was discharged from the ED the following day with ambulatory follow-up. A repeat thoracic CT performed two weeks later demonstrated that the findings identified in the first CT had resolved. Pneumopericardium, -mediastinum, and -thorax are rare conditions reported after cocaine abuse. A conservative approach with a period of observation in a suitable ambulatory unit is acceptable, as current literature suggests that the condition is usually self-limiting.